(untitled) (Research, Society and Development, 2025)
Objective: To analyze the temporal and regional trends of hospitalizations due to Acute Myocardial Infarction (AMI) in Goiás, Brazil, between 2017 and 2023, considering sex, age group and associated risk factors. Methods: Ecological, descriptive and analytical study, with secondary data from the SUS Hospital Information System (SIH/DATASUS). Hospitalizations due to AMI (ICD-10: I21) were analyzed, stratified by year, sex, age group and health macro-region. Hospitalizations due to systemic arterial hypertension (SAH), diabetes mellitus (DM) and obesity were also included. Statistical analysis used absolute and relative frequencies, in addition to the chi-square test for temporal trends and association between categorical variables. Results: During the analyzed period, hospitalizations due to AMI increased by 131%, with a predominance in men (62.3%) and individuals aged 60 to 69 years (29.0%). The Central-West macro-region accounted for 41.7% of cases. There was a 644% increase in hospitalizations due to obesity and a 55.8% reduction due to hypertension. All associations analyzed were statistically significant (p < 0.001). Conclusion: The study reveals a significant increase in hospitalizations due to AMI in Goiás, with significant regional and demographic disparities. The findings reinforce the need for regional prevention strategies integrated with primary health care.